2020
DOI: 10.1111/and.13798
|View full text |Cite
|
Sign up to set email alerts
|

Does sperm DNA fragmentation have negative impact on embryo morphology and morphokinetics in IVF programme?

Abstract: Evaluation of sperm integrity may predict the in vitro fertilisation (IVF) outcomes. The aim was to evaluate the relationship between the sperm DNA fragmentation (sDNAf) with embryo morphology and morphokinetic using time‐laps monitoring (TLM) and to select the best time points for normalisation in IVF setting. After evaluating the fertilisation and pronuclei (Z) scoring, 328 normally fertilised oocytes were assessed to time of pronuclei fading, time of 2 to 8 discrete cells (t2–t8) and abnormal cleavage patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 39 publications
(41 reference statements)
0
9
0
Order By: Relevance
“…There is a positive correlation between the incubation time and sperm DNA damage. Prolonged incubation of prepared sperm samples at 37°C was associated with high rates of sperm DNA fragmentation, indicating that the sperm samples intended for ART procedures should be used within 2 hours of incubation at 37°C [33,34] . Interestingly, it has been shown that following 2 and 4 hours of incubation at RT, the sperm progressive motility and viability decreased significantly [35] .…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive correlation between the incubation time and sperm DNA damage. Prolonged incubation of prepared sperm samples at 37°C was associated with high rates of sperm DNA fragmentation, indicating that the sperm samples intended for ART procedures should be used within 2 hours of incubation at 37°C [33,34] . Interestingly, it has been shown that following 2 and 4 hours of incubation at RT, the sperm progressive motility and viability decreased significantly [35] .…”
Section: Discussionmentioning
confidence: 99%
“…Finally, after a brief wash and dehydration in increasing ethanol baths, the sperm chromatin was stained for visualization under bright-field microscopy. The spermatozoa were scored under the light microscope (×1000) and big or medium halos were considered as spermatozoa without DNA fragmentation while fragmented spermatozoa showed small or no halos ( 18 ).…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies emphasize the direct relationship between SDF and male infertility and increased miscarriage rate after IVF or ICSI [ 50 ]. Whereas low SDF can be repaired by the competent oocyte, high levels of SDF were correlated with embryo morphokinetic delay observable from the time of of pronuclei fading to the morula stage [ 51 , 52 , 53 , 54 ]. The consequences are lower blastulation and pregnancy rates [ 55 ].…”
Section: Spermatozoon Effect On Embryo Developmentmentioning
confidence: 99%